Pengaruh Metode Membaca Survey Question Read Recite Recall (SQ3R) Terhadap Hasil Belajar Mata Pelajaran Bahasa Indonesia Materi Teks Pengumuman - Mahyudin Mahyudin; Endang Yuda Nuryenda; Sri Hastuti (Journal of Elementary Education Research, 2022)
Most students consider Indonesian language lessons to be boring lessons so that it has an impact on students' low interest in learning which leads to student learning outcomes that are still below the school's Minimum Completeness Criteria. One alternative so that learning Indonesian is not boring is to use the method of reading the Survey Question Read Recite Recall (SQ3R). SQ3R reading method is a reading method to find main ideas and supporting main ideas. This study aims to determine the response and influence of the SQ3R reading method in learning Indonesian language announcement text material on student learning outcomes. This type of research is a quasi-experimental research. The sampling technique uses saturated sampling. The population and sample are fourth grade students of SD Negeri 1 Bendungan with a total of 34 students. The sample was divided into 2 groups, namely the experimental class and the control class. The sampling technique used a questionnaire and a test which was analyzed descriptively and using the t test. Analysis of the questionnaire data from 14 students showed that 84.1% of students had a positive response to the SQ3R method. The results of the t-test show that tcount ≥ ttable (t2,848 ≥ t2,074 ) so that H1 is accepted. Control N-gain Experimental N-gain (0.57 0.69) means that there is a difference in student learning outcomes with the SQ3R reading method and lectures. So, students responded positively to the SQ3R reading method and this method had an effect on student learning outcomes.